Funkcjonariusze służb specjalnych w późnym Cesarstwie - "agentes in rebus" - Pikulska-Robaszkiewicz, Anna (Prawo Kanoniczne, 1994)
The agentes in rebus corps (schola agentum in rebus) was mentioned for the first time in AD 319. Post services were the main duty of the functionaries. The services included mail delivery, public post supervision, and general police discretion that was equal to spying for emperors. Occasionally, the agents were obliged to provide special services, e.g. executions of death penalty on high rank officials. The functionaries were universally hated because of their greed, their corruption and the nature of their services. Additionally, schola agentum in rebus had become an asylum for various kinds of dregs and scummings. Although emperors decided to impose limits on the agents’ number and on the nature of services, in order to improve the situation, the activity they undertood did not cause the desired effects. The corps structure allowed an efficient information flow. Nevertheless, the fusion of courier and intelligence functions was regerded natural at that time.